Social media for energy saving campaigns - Rahmawati, Yuni; Fatimah, Siti; Harianja, Candra Friyandi; Noor , Zaka M.; Aulia, Shafa T. (Bulletin of Social Informatics Theory and Application, 2021)
The demand for electrical energy continues to increase in line with technological developments. Electrical energy generally comes from fossil fuels or coal. The higher the electricity demand, the more carbon emissions are produced, which can cause global warming. Currently, many campaigns invite people to save energy. The campaign is carried out using social media. Currently, 170 million active social media users in Indonesia spend 3 hours 14 minutes accessing social media. This phenomenon opens up great opportunities for business people, organizations, institutions, and the government to carry out a campaign or promotional activities, such as energy-saving campaigns by various organizations with social media such as Facebook, Instagram, Twitter, and Youtube. This research aims to observe government and non-government accounts that are campaign energy saving on Facebook, Instagram, Twitter, and Youtube. This research was conducted by collecting data from the followers or subscribers, time the account operates on each social media, post, and other necessary data. Based on social media research, the most effective way to campaign energy saving is Instagram.